La astenia tumoral: un síndrome poco estudiado - Gónzalez Barón, Manuel; Ordóñez, Amalio (Psicooncología, 2004)
Fatigue is one of the most common symptoms in patients with cancer. Doctor have not paid much attention to it for years, probably because there were not therapeutic options in many cases. We hereby revise the features of this syndrome: definition, pathogenesis, epidemiology, biochemical markes and treatment. We have summarised the main conclusions from our book “Tumoral fatigue”, the first written in Spanish about this topic, which is framed in the recently created Asthenos group.